Association between Thyroid Stimulating Hormone and Lipid Accumulation Product in Hypothyroid and Euthyroid Adults in Nepal - Pandey, Rachana; Badal, Nibidha; Shrestha, Jyoti; Yadav, Rahul Kumar (Nepal Journal of Health Sciences, 2025)
Introduction: Hypothyroidism adversely affects lipid metabolism and increases cardiovascular risk. The Lipid Accumulation Product index, based on waist circumference and triglycerides levels, is a simple marker of central lipid accumulation. Hormone deficiency in hypothyroidism leads to elevated cholesterol and triglycerides, both of which contribute to higher lipid accumulation product scores. Exploring this association may provide insight into the cardio metabolic burden of thyroid dysfunction.Objective: To compare the Lipid Accumulation Product Index in hypothyroid and Euthyroid adults and assess its correlation with serum Thyroid Stimulating hormone level.Methods: Cross-sectional comparative study conducted at Dhulikhel Hospital in 130 hypothyroid and 130 euthyroid adults after ethical clearance from Institutional review committee, Kathmandu University School of medical Sciences. Lipid Accumulation Product was calculated using standard gender-specific formulas. Statistical analysis was performed using Spearman correlation and logistic regression.Results: Median Lipid Accumulation Product is higher in the hypothyroid group (54.1) compared to the euthyroid group (38.3), suggesting that hypothyroid patients tend to have greater lipid accumulation (p < 0.001). Thyroid Stimulating hormone was significantly associated with Lipid Accumulation Product even after adjustment for age and sex (p < 0.05).Conclusion: Patients with hypothyroidism have significantly higher levels of Lipid Accumulation Product index. Thyroid Stimulating hormone and lipid accumulation product are positively correlated, supporting it as a metabolic risk marker in thyroid dysfunction.